The math book - Dangerfield, Janet; Davis, Heather (Mathematics teacher); Farndon, John; Griffiths, Jonny; Jackson, Tom, 1972-; Patel, Mukul; Pope, Sue, 1959- (Big ideas simply explained., 2019)
Presents a chronological history and explanation of mathematical discoveries and concepts, from the discovery of simple numbers and addition in ancient times up to modern mathematicians of importance, like Alan Turing and his invention of the Turing Machine. Includes a glossary.